Review of Robotic-Assisted Surgical Procedures Available in Poland - Suława, Adrian; Fedorowicz, Sebastian; Madej, Adrianna; Targoński, Oskar; Targońska, Marta; Furgalska, Julia; Basiak, Aneta; Ptasiński, Aleksander; Niekurzak, Rafał; Buczek, Agnieszka (Quality in Sport, 2024)
Introduction and purpose: Surgical robots are gaining increasing acceptance and utilization in the medical world. This trend is also notable in Poland, where both the prevalence and application of surgical robots have notably risen, establishing them as integral components of patient care. Our study aims to evaluate the current literature on robotic-assisted surgery available in Poland using the PubMed database. We aim to clarify the advantages of this approach over traditional methods and other minimally invasive techniques. State of knowledge: In Poland, we have three registered and widely available surgical robotic-assisted procedures intended for the treatment of prostate cancer, colorectal cancer, and endometrial cancer. Robotic surgery represents a significant advancement in the surgical treatment of cancers for both patients and surgeons. By enhancing precision and providing a more comfortable and efficient working environment, robotic surgical systems improve patient outcomes and offer substantial advantages to surgical teams. Summary: The major benefits of robotic surgery are short-term outcomes including reduced blood loss, shorter hospital stays, and fewer postoperative complications. When it comes to long-term outcomes differences are not such significant. What needs to be clarified is the potential advantages over conventional laparoscopic techniques in future studies to define the role of robotic surgery in different cancer treatment algorithms.